Proyecto de factibilidad para instalar una empresa productora de mermelada en cuanto a los aspectos de mercado, técnico y su rentabilidad económica en el cantón Quevedo 2012 - Cedeño Vera, Angel Miguel (2013)
The micro company to elaborate and to commercialize jams with flavor to tropical fruits will establish in the city of Quevedo province of the rivers with the intention of offering to the consuming market a specialized product using raw material of the zone. The jams will have a great acceptance since in agreement to the realized offer this type of product is liked by the persons who pay a fixed price and eat what they wish; in addition rapidity exists in the service and variety in the flavor. It is important to highlight that the jams of pineapple, small peach, bramble it dwells. They have acceptance on the market, children and to adult persons like it so much for his contained nutritional high place. The micro company motive of this project needs of a total initial investment of $ 28107.84 of which his owner was contributing with 18107.84 $ and the remaining contribution of $ 10000 term will be financed by a credit of the public local banking to 4 and an interest of 15 %. The opportunity to install this type of restaurant is very important since it represents an opportunity of business and in addition it is an investment that still has not been exploited in this city.